2003
DOI: 10.1002/cne.10788
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of presynaptic delta opioid receptors in the ventrolateral periaqueductal gray after swim stress

Abstract: Immunolabeling for the delta opioid receptor (DOR) is localized primarily to axon terminals in the ventrolateral periaqueductal gray (vlPAG). However, rather than on the plasma membrane, DOR immunoreactivity is usually located within the cytoplasmic compartment, often associated with dense-core vesicles. In this study, the hypothesis that a behavioral stimulus, a cold water swim stress (3 minutes at 4 degrees C; CWSS), could initiate the translocation of the DOR was tested. The subcellular distribution of DOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 49 publications
4
48
0
Order By: Relevance
“…The present results provide evidence for the physiological significance of recent reports that prolonged MOPr agonist exposure induces translocation of DOPrs from the cytosol to the plasma membrane (Cahill et al, 2001a;Morinville et al, 2003). In the PAG of untreated animals, the DOPr is primarily localized in axon terminals (Arvidsson et al, 1995;Kalyuzhny et al, 1996;Kalyuzhny and Wessendorf, 1998) Under these conditions, DOPrs in the PAG are rarely observed on the plasma membrane but are primarily associated with intracellular membranes (Commons et al, 2001;Commons, 2003). The intracellular localization of DOPrs is consistent with previous studies suggesting that DOPr agonists have zero or low efficacy in the PAG region at the cellular and systems level in untreated animals (Rossi et al, 1994;Ossipov et al, 1995;Vaughan et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present results provide evidence for the physiological significance of recent reports that prolonged MOPr agonist exposure induces translocation of DOPrs from the cytosol to the plasma membrane (Cahill et al, 2001a;Morinville et al, 2003). In the PAG of untreated animals, the DOPr is primarily localized in axon terminals (Arvidsson et al, 1995;Kalyuzhny et al, 1996;Kalyuzhny and Wessendorf, 1998) Under these conditions, DOPrs in the PAG are rarely observed on the plasma membrane but are primarily associated with intracellular membranes (Commons et al, 2001;Commons, 2003). The intracellular localization of DOPrs is consistent with previous studies suggesting that DOPr agonists have zero or low efficacy in the PAG region at the cellular and systems level in untreated animals (Rossi et al, 1994;Ossipov et al, 1995;Vaughan et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, stressful stimuli as brief as 3 min have been shown to induce translocation of DOPr to the surface membrane of PAG nerve terminals in previous studies (Commons, 2003). Slices of PAG from control mice were incubated in morphine (5 M) in vitro for 1-3 h, followed by superfusion of CTAP (1 M).…”
Section: Dopr Agonists Inhibit Gabaergic Synaptic Transmission Only Amentioning
confidence: 96%
“…Recent anatomical studies have shown stimulus-dependent translocation of -and ␦-opioid receptors to the plasma membrane in both posterior pituitary and periaqueductal gray neurons (Shuster et al, 1999;Commons, 2003). To our knowledge, however, trafficking and insertion of -opioid receptors has not yet been reported.…”
Section: Introductionmentioning
confidence: 92%
“…Anatomical studies have shown that presynaptic opioid receptors might be associated with dense-core vesicles, where the ␣ subunits of G-proteins might also be localized (Aronin and DiFiglia, 1992;Cheng et al, 1995;Drake et al, 1996;Zhang et al, 1998;Shuster et al, 1999;Commons et al, 2000;Commons, 2003). This type of association raises the possibility that G-protein-mediated activity may modulate receptor functions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CNS expression of DORs is often dynamically induced following physiological challenge (Commons, 2003;Hack et al, 2005;Cahill et al, 2007) and trafficking to the plasma membrane is regulated through a variety of mechanisms, which are dependent on stimulus type and duration (Cahill et al, 2007). Although previous studies have identified a role of the DOR in opioid tolerance and dependence (Gomes et al, 2004;Zhang et al, 2006), and have suggested that DOR activity modulates both food consumption and drug reward (Duvauchelle et al, 1996;Kelley et al, 1996;Ragnauth et al, 1997;Suzuki et al, 1997;Lamonte et al, 2002;Khaimova et al, 2004), to date no one has specifically investigated the possible protective effects of the DOR on drug or ethanol (EtOH) consumption.…”
Section: Introductionmentioning
confidence: 99%